2001
DOI: 10.1002/jbm.1230
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic heat production as a measure of macrophage response to particles from orthopedic implant materials

Abstract: An in vitro method to gauge metabolic heat response of macrophages (MØ) to particulates is described. Whereas the majority of work cited relies on chemical analysis to assess MØ response to particles, we have used isothermal microcalorimetry (IMC) for direct continuous measurement of metabolic heat production to gauge the response. IMC is a screening method, in that it ensures that no energy-consuming phagocytic response goes undetected, and that the aggregate metabolic magnitude of the responses is determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…We have examined IC-21 macrophages after particle exposure in a related study 17 and showed by confocal microscopy that phagocytosis does indeed occur with these particles and this macrophage cell line. Also, the various changes in macrophage secretory responses suggest that binding of LPS to both HDPE and Co alloy particles (as well as to planar surfaces of polypropylene) occurred.…”
Section: Discussionmentioning
confidence: 98%
“…We have examined IC-21 macrophages after particle exposure in a related study 17 and showed by confocal microscopy that phagocytosis does indeed occur with these particles and this macrophage cell line. Also, the various changes in macrophage secretory responses suggest that binding of LPS to both HDPE and Co alloy particles (as well as to planar surfaces of polypropylene) occurred.…”
Section: Discussionmentioning
confidence: 98%
“…These studies have examined activation of signal transduction pathways, 40 -42 metabolic activity, 43 and production of proinflammatory cytokines 41,[43][44][45][46][47] and have examined virtually all orthopedically relevant types of particles, including titanium, 42,44,47 cobaltchrome, [43][44][45] PMMA, 40,42,46 polyethylene, 43,45 and hydroxyapatite. 42 Most importantly, Akisue et al 41 have further extended these studies to include authentic titanium alloy particles retrieved from patients with aseptic loosening.…”
Section: Endotoxin Increases Biological Activity Of Wear Particles Inmentioning
confidence: 99%
“…The heat source production value used in this study resulted in temperature differences that approximate the values that have been reported in literature most recently. This value, 5 mW mm À3 , is higher than macrophage heat production values that have been reported in literature (Thore´n et al, 1990;Charlebois et al, 2002). In addition, the catheter geometry was simplified, whereas in reality it can be more complex.…”
Section: Discussionmentioning
confidence: 60%